2021
DOI: 10.2478/hepo-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and awareness of medicinal plants in treatment of kidney lithiasis in eastern Morocco: a retrospective study

Abstract: Summary Introduction: Kidney stone is a major public health problem. Over 5% of the population is affected by kidney stones, with causes a lifetime risk of transmitting renal lithiasis of about 8 to 10%. Objective: The goal of our study is the attitude and awareness of lithiasis patients regarding the use of medicinal plants in eastern Morocco. Methods: We carried out a study on lithiasis patients to retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Herbal medicine is an integral part of the cultural practices of our local communities, which constitute an important heritage for the management of urological diseases (Bencheikh et al, 2021;Guerrouj et al, 2021). In recent years, various plants and traditional medicines have been proposed to reduce calcium oxalate kidney stones, which can be useful in its prevention and treatment (Afkari et al, 2019).…”
Section: Kinetic Evolution Of Ph and Evaluation Of The Dissolution Ca...mentioning
confidence: 99%
“…Herbal medicine is an integral part of the cultural practices of our local communities, which constitute an important heritage for the management of urological diseases (Bencheikh et al, 2021;Guerrouj et al, 2021). In recent years, various plants and traditional medicines have been proposed to reduce calcium oxalate kidney stones, which can be useful in its prevention and treatment (Afkari et al, 2019).…”
Section: Kinetic Evolution Of Ph and Evaluation Of The Dissolution Ca...mentioning
confidence: 99%
“…Medicinal and aromatic herbs are widely used by the world's population due to their abundance of secondary metabolites, which serve as the foundation for many medical therapies. 1 , 2 Secondary metabolites exhibit several potential biological properties; this forms the scientific basis for the use of herbs in folk medicine. These metabolites have been described as antivirals and antibiotics and they allow good absorption of UV radiation; furthermore, it has been demonstrated that some herbs can play a key role in animal reproduction by exhibiting estrogenic properties.…”
Section: Introductionmentioning
confidence: 99%